Analysis of selected pesticides and alkylphenols in human cord blood by gas chromatograph-mass spectrometer - Tan, B.L.L.; Mohd, M.A. (2003)
A total of seven pesticides and eight alkylphenols were monitored using this method for the determination of their trace levels in human cord blood. The pesticides are lindane, diazinon, alpha-endosulfan, beta-endosulfan, endosulfan sulfate, chlorpyrifos and endrin; while the alkylphenols are 4-n-butylphenol, 4-n-pentylphenol, 4-n-hexylphenol, 4-toctylphenol, 4-n-heptylphenol, nonylphenol, 4-n-octylphenol and bisphenol A. The pesticides and alkylphenols in the cord blood samples were extracted with solid phase extraction IST C18 cartridges and analyzed by selected ion monitoring mode using quadrapole detector in Shimadzu QP-5000 gas chromatograph-mass spectrometer. Trace levels of pesticide and alkylphenols in the range of non-detectable to 15.17 ng ml(-1), were detected in the human cord blood samples. This technique of monitoring the levels of endocrine-disruptors in blood samples is consistent, reliable and cost effective while reducing wastage of time and solvents. (C) 2003 Elsevier Science B.V. All rights reserved.